2021
DOI: 10.3390/w13030266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Combined Utilization of Ultrasonic/Hydrogen Peroxide on Excess Sludge Destruction

Abstract: Excess sludge reduction has been a research hotspot for a long time. Ultrasonic treatment of excess sludge was an efficient and green pretreatment method, and also can be combined with the addition of oxidants. To improve the effect of ultrasound treatment on sludge destruction, hydrogen peroxide (H2O2) was added to examine the combined results in the current study. The effects of the ultrasound/hydrogen peroxide system on the release of sludge organic matter during the destruction process were studied. Single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…At the same time, keeping the pH value at 12 requires more chemical consumption and keeping the pH at this value is very difficult in terms of operating. The pH = 11 value chosen in this study was the same as the selected pH value in previous similar studies [39,40]. Lv et al [33] The reaction time chosen for sludge disintegration in this study was 60 min.…”
Section: Selection Of Reactor Operating Parametersmentioning
confidence: 99%
“…At the same time, keeping the pH value at 12 requires more chemical consumption and keeping the pH at this value is very difficult in terms of operating. The pH = 11 value chosen in this study was the same as the selected pH value in previous similar studies [39,40]. Lv et al [33] The reaction time chosen for sludge disintegration in this study was 60 min.…”
Section: Selection Of Reactor Operating Parametersmentioning
confidence: 99%
“…They found that with an initial pH level of 11.0, 0.5 mmol/L H 2 O 2 concentration, 17 g/L sludge concentration and 15 min US treatment (40 kHz), ∆SCOD reached 3662.78 mg/L, with a DD of 28.61% and a sludge reduction rate of 19.47%. [79].…”
Section: Ultrasound-h 2 O 2 Combined Treatmentmentioning
confidence: 99%